2018
DOI: 10.1590/0370-44672017710175
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and mechanical analysis of 316L SS/ β-TCP composites produced though the powder metallurgy route

Abstract: The 316L stainless steel (316L SS) is one of the most used metallic materials for implants, due to its high mechanical properties and low cost. However, it is bioinert. One possibility to improve its biocompatibility is the production of a composite with β-tricalcium phosphate (β-TCP) addition. This study investigated the mechanical behavior of 316L SS/β-TCP composites through powder metallurgy. For this, used were 3 compositions, with 0 %, 5 % and 20 % of β-TCP. The compositions with 5% and 20% were milled du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…4d ). The effects of volumetric densities of 316L and HAp on the mechanical properties are available elsewhere 28 . Energy-dispersive X-ray spectroscopy (EDS) results confirm the presence of calcium and phosphorus in small amounts (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4d ). The effects of volumetric densities of 316L and HAp on the mechanical properties are available elsewhere 28 . Energy-dispersive X-ray spectroscopy (EDS) results confirm the presence of calcium and phosphorus in small amounts (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Kuffner et al (2018) investigated the reuse of metallic scraps of AISI 52100 tool steel, and the elastic modulus obtained for the sintered material were of 1.8 GPa (without addition of alumina in the milling process) and 2.5 GPa (with addition of 3% of alumina). In another study, carried out by Faria et al (2018), in which they reused 316L stainless steel, the elastic modulus found was also low, corresponding to approximately 3% of the value of the material as casted. They verified the relationship between porosity and elastic modulus, and concluded that the samples with the highest pore volume were those with the lowest elastic modulus.…”
Section: Hardness Testmentioning
confidence: 95%